To the best of Minerva Divine Mother of Wisdom: Panegyric to Our Lady of the Snows at the University of San Marcos in 1721 - Flórez, Gloria Cristina (2019)
Marian devotion is one of the most important of Christianity and its development and evolution has been related to different situations lived through centuries in different geographical spaces. The cult of Our Lady of the Snows was established in our territory since the 16th Century, and is of great importance for our University as can be seen in the documentation referring activities offered in her honor. It’s of great importance to study the sermon given at a party held at the Cathedral of Lima on August 5, 1721 and Dr. Juan de Sarricolea, Professor of Theology was in charge, later he became Bishop in Santiago de Chile and in Cuzco.